PTU-006 The Value of EUS in Diagnosing Liver Hilar Lesions. (17th August 2016) - Maher, B; Forde, C; Pallan, A; Boulton, R; Shekhar, C; Mahon, BS
Abstract : Introduction: The aetiology of liver hilar strictures remains a challenging area to diagnose. Advances in cross sectional imaging have improved our ability to better delineate these lesions. However, in the absence of a significant mass, benign and malignant disease may demonstrate similar imaging features, underlining the importance of obtaining a definitive tissue diagnosis prior to potential surgery or chemotherapy. As both treatments carry significant morbidity, and mortality in the case of surgery, obtaining an accurate diagnosis remains imperative. Obtaining a pathological diagnosis remains challenging in particular as the liver hilum is not easily amenable to percutaneous tissue sampling. The yield of endobiliary techniques, principally ERCP guided brushings and endobiliary biopsy is reported to range widely between 33% and 80%, and in practice remains low. Although these methods are highly specific for diagnosis of malignancy, they have a low sensitivity, ranging between 46% and 73%. EUS is a powerful tool in the assessment of hilar lesions with an ability to perform FNA and obtain tissue. We sought to assess the ability of EUS to make a positive diagnosis in these lesions. Methods: A retrospective review was performed on all patients who were referred with a hilar mass or stricture that proceeded to EUS assessment between 2009 and April 2015. Hilar lesions were defined as those involving the common hepatic duct (i.e. proximal to the cystic duct insertion) and/or confluence of the right and left intrahepatic ducts. Assessment involved review of patient medical records, EUS findings, cytological results, pre and post procedure imaging up to 12 months post EUS FNA and clinical outcomes. Results: 129 patients underwent EUS FNA, of which 76 were male, 53 were female and the mean age was 61 years old. 3 patients were excluded due to lack of follow up data. 87 (67.4%) patients were diagnosed with malignant disease, of which 93% had cholangiocarcinoma. 83% of those with a positive diagnosis were acquired in the first biopsy. EUS FNA had a sensitivity of 83%, specificity of 100%, positive predictive value of 100% and a negative predictive value of 66%. Conclusion: This is the largest such series to date in the published literature. In obtaining a diagnosis from a hilar lesion, EUS proves superior to other techniques such as endobiliary biopsy. It is a highly sensitive and specific technique and should be considered as a first line in assessment of lesions in this challenging area. Disclosure of Interest: None Declared